Examining Singapore’s intercultural business communication using intercultural communication competency framework. - Ng, Noel Jia Wei. (2013)
Intercultural communication is defined the interactions with members of other cultures. Despite the complexity involved in intercultural communication, it has often been viewed favorably and highly encouraged in some business organizations because of the inherent advantages of having diversity in a group. Multicultural group discussions could potentially lead to more ways of viewing the problem or situation and they tend to be more creative. In order to appreciate and enhance the chances of successful intercultural communication, many intercultural communication competency (ICC) models have been developed by various researchers. ICC refers to ability to execute communication behaviors effectively and appropriately by the negotiation of their own cultural identities in a culturally diverse environment